Shorting the bear: A test of anecdotal evidence of insider trading in early stages of the sub-prime market crisis - Les Coleman; Adi Schnytzer (Bar-Ilan University, Department of Economics, 2011)
This article uses trading data in the options market for shares in The Bear Sterns Companies (BSC) during the early stages of the US sub-prime crisis as a laboratory to examine the incidence of insider trading. We take the perspective of a regulator making use of hindsight to identify the most propitious periods for insider trades and to identify market activity indicative of insiders. Half the value of options traded were on 19 percent of the days, mostly in contracts in or close-to the money and near to expiry. We find persuasive evidence that insiders could have been active in trading Bear Sterns stock during this period.
Keywords: 330; insider trading; forensic finance; Bear Sterns; Insiderhandel; Finanzkrise; USA